Effects of Social Support, Perceived Threat, and Witnessing Death on the Risk of Post-Traumatic Stress Disorder: Meta-Analysis - Fatimah Hasna Karima; Argyo Demartoto; Bhisma Murti (Journal of Epidemiology and Public Health, 2023)
Background: Post-traumatic Stress Disorder (PTSD) is an anxiety disorder that can develop after exposure to horrific events and experience a series of reactions after repeated trauma, stress, and scary thoughts. The risk of PTSD is influenced by several factors such as social support, perceived threat, and witnessing death. The purpose of this study was to estimate the effect of social support, perceived threat, and witnessing death on the risk of PTSD using a meta-analysis of primary studies conducted by previous authors. Subjects and Method: This was a systematic review and meta-analytic study. This study used the PICO model. The meta-analytic study was carried out by searching for articles from databases in electronic form using Google scholar, PubMed, and Elsevier. An article search was conducted from 1 to 28 February 2023. The keywords used were “Post-traumatic Stress Disorder” OR “PTSD” AND “Social Support” AND “Witnessing death” AND “Perceiving threat” AND “Multivariate” AND “Cross-Sectional”. The inclusion criteria for this study were complete articles using cross-sectional research, published in 2013-2023. Analysis of the articles in this study used RevMan 5.3 software. Results: A total of 22 cross-sectional studies from North America, South America, Europe, Africa and Asia were selected for thi study. Social support has a lower risk of experiencing PTSD by 0.38 times compared to people who do not receive social support (aOR=0.38; 95% CI= 0.18 to 0.77; p= 0.007). People with perceived threats have a risk of experiencing PTSD by 2.29 times compared to people without perceived threats (aOR= 2.29; 95% CI= 1.58 to 3.33; p<0.001). People who witness death have a risk of experiencing PTSD by 1.63 times compared to people who do not witness death (aOR= 1.63; 95% CI= 1.23 to 2.15; p<0.006). Conclusion: Social support can significantly reduce the risk of PTSD. Perceived threat and witnessing death can significantly increase the risk of PTSD. Keywords: PTSD, post-traumatic stress disorder, social support, perceived threat, witnessing death Correspondence: Fatimah Hasna Karima. Masters Program in Public Health. Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: fatimahhasna01@gmail.com. Mobile: +6281215184110.